Iron phytostabilization by Leucaena leucocephala - Bomfim, Nayane Cristina Pires [UNESP]; Aguilar, Jailson Vieira [UNESP]; de Paiva, Wesller da Silva [UNESP]; de Souza, Lucas Anjos; Justino, Gilberto Costa; Faria, Glaucia Amorim [UNESP]; Camargos, Liliane Santos [UNESP] (Elsevier, 2021)
This study investigated the potential for tolerance, absorption, and translocation of iron (Fe) by Leucaena leucocephala, as well as the response of the photosynthetic mechanism and the phytoremediation potential of L. leucocephala grown in soil with concentrations of Fe (0, 100, 200, 300, 400, and 500 mg Fe/dm3 of soil). The chlorophyll content and the photosynthetic apparatus showed a significant difference between treatments: the chlorophyll content, transpiration rate, and stomatal conductance were higher in the treatment 200 mg Fe/dm3 of soil, while the photosynthetic rate was higher in the treatment 500 mg Fe/dm3 of soil in relation to the control. From 300 mg Fe/dm3 of soil onward, there was a significant reduction in the number of leaves, mass, and biomass of L. leucocephala. The species is tolerant to the Fe doses analyzed. Availability of Fe in the soil after the cultivation of L. leucocephala decreased, evidencing the plant capacity of Fe absorption, which accumulated mostly in the roots, and only % of Fe was translocated to the shoots. The highest Fe accumulation per biomass was 9.48 mg, at 200 mg Fe/dm3 of soil. The amount of Fe translocated and accumulated in L. leucocephala is directly related to its biomass production thus the dose 200 mg Fe/dm3 of soil allows the best performance of phytoremediation potential. Although plant growth is affected by treatments of 300, 400 and 500 mg Fe/dm3 of soil and Fe accumulation is less, L. leucocephala is able to tolerate and phytostabilize soil Fe with potential for use in phytoremediation, mainly because it is a kind of phytostabilization of Fe.
Keywords: Biomass; Phytoremediation; Potential toxic elements; Soil remediation; Tolerance